Improving Elementary School Students' Reading Skills Using Picture Word Cards: How is This Possible? - Yunisa; Lubis, Azmil Hasan (MANDAILING GLOBAL EDUKASIA, 2024)
Reading ability is one of the abilities that students must master at elementary school level. This research aims to improve students' reading skills by using picture cards as media. This research is a mixed research type of classroom action research. The design used is the Kemmis & Mc Taggart design with four steps, namely planning, action, observation and reflection. The focus of this research was on 12 male and 11 female students who were in class 1 of SDN 017 Petung, Penajam Paser Utara. Data was collected using interview, observation and test techniques. The data obtained were analyzed using descriptive statistical techniques. The results of classroom actions show that using picture cards can help students read better. The results of the first cycle test show this: 15 out of 23 students achieved individual completion with a classical acceptance rate of 63.75% and a classical pass rate of 55.00% at the initial stage. However, in the second cycle, the test results showed that 20 out of 23 students succeeded in achieving individual completeness, with an average score of 9.95 and achieving classical completeness of 95%. Grade 1 students at SDN 017 Petung Penajam Paser Utara can use picture cards to improve their reading skills. The research results showed that the activities of teachers and students during learning activities showed an increase in the category from adequate in cycle I to very good in cycle II. Based on these results, it can be concluded that the use of picture cards is effective in improving students' reading skills.